2021
DOI: 10.1016/s2589-7500(21)00205-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning-based synthesis of post-contrast T1-weighted MRI for tumour response assessment in neuro-oncology: a multicentre, retrospective cohort study

Abstract: Background Gadolinium-based contrast agents (GBCAs) are widely used to enhance tissue contrast during MRI scans and play a crucial role in the management of patients with cancer. However, studies have shown gadolinium deposition in the brain after repeated GBCA administration with yet unknown clinical significance. We aimed to assess the feasibility and diagnostic value of synthetic post-contrast T1-weighted MRI generated from pre-contrast MRI sequences through deep convolutional neural networks (dCNN) for tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 26 publications
4
55
0
2
Order By: Relevance
“…To mitigate this, previous studies have shown that missing MRI sequences may be synthesized using generative adversarial networks. 34 , 35 Consequently, this may enable the use of HD-BM even with incomplete and heterogeneous sequence protocols.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate this, previous studies have shown that missing MRI sequences may be synthesized using generative adversarial networks. 34 , 35 Consequently, this may enable the use of HD-BM even with incomplete and heterogeneous sequence protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The GAN utility is an image-to-image translation task, which is useful for generating synthetic data to fill in absent or insufficient data in a multicenter trial. Jayachandran et al [ 41 ] explored the synthesis of post-contrast MRI sequences from pre-contrast MRI sequences alone by filling in absent imaging data without the use of the gadolinium-based contrast agent during MRI. The study incorporated MRI data from three phase 2 and 3 clinical trials with >2,000 patients.…”
Section: Future Use Case: Image Generationmentioning
confidence: 99%
“…Recently, Jayachandran Preetha et al [ 17 ] investigated the synthesis of post-contrast MRI sequences using pre-contrast MRI sequences, filling in the absence of imaging data for imaging evaluation of glioblastoma ( Fig. 1 ).…”
mentioning
confidence: 99%
“…From this hypothesis-generating study [ 17 ], we can obtain ideas about how to apply and validate GANs in clinical cases. First, synthetic images can be used as direct substitutes for real images and can make the use contrast media for MRI or CT imaging or an additional radiation exposure for X-ray, CT, or PET imaging optional, thereby reducing the harm or cost associated with the extra imaging procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation